Different types of components obtained from Monascus purpureus with neuroprotective and anti-inflammatory potentials. Issue 18 (6th August 2021) - Wu, Ho-Cheng; Chen, Yih-Fung; Cheng, Ming-Jen; Wu, Ming-Der; Chen, Yen-Lin; Chang, Hsun-Shuo
Abstract : Seven new and ten known compounds were isolated from a citrinin-free strain: M. purpureus BCRC 38110. The bioactivity results indicated that this strain possessed potentials against inflammatory osteoarthritis and paclitaxel-induced neurotoxicity. Abstract : The mold Monascus has been used as a natural food coloring agent and food additive for more than 1000 years in Asian countries. In Chinese herbology, it was also used for easing digestion and antiseptic effects. Through a thorough investigation of a citrinin-free strain: M. purpureus BCRC 38110, four azaphilones, three benzenoids, one benzofuranone, one 5′, 6′-dihydrospiro[isochromane-1, 2′-pyran]-4′(3′ H )-one derivative, two steroids, and six tetralones have been successfully identified. Among them, monapyridine A (1 ), monatetralones A–E (2–6 ), and monabenzofuranone (7 ) were first reported. Their structures were characterized by 1D and 2D NMR, UV, IR, and HRESIMS analyses. With a series of bioactivity screening, monascuspirolide B (14 ) and ergosterol peroxide (16 ) exhibited concentration-dependent attenuation of the paclitaxel-induced neurite damage of mouse dorsal root ganglion neurons. The interleukin (IL)-1β-induced release of inflammatory cytokines IL-8 and tumor necrosis factor (TNF)-α in human chondrosarcoma cells was inhibited by monapurpureusone (8 ) and monascuspirolide B (14 ). Altogether, M. purpureus BCRC 38110 possessed potentials as natural therapeutics against inflammatory osteoarthritis and paclitaxel-induced neurotoxicity.